An examination of affect prior to and following episodes of getting drunk in women with bulimia nervosa. (30th June 2016) - Pisetsky, Emily M.; Crosby, Ross D.; Cao, Li; Fitzsimmons-Craft, Ellen E.; Mitchell, James E.; Engel, Scott G.; Wonderlich, Stephen A.; Peterson, Carol B.
Abstract: The current study examined the association between affect and self-reported alcohol intoxication in women with bulimia nervosa (BN; N =133). Participants completed a two-week ecological momentary assessment protocol. Momentary global positive affect (PA) and negative affect (NA), as well as the facets of NA (fear, guilt, hostility and sadness), were measured. Forty-five participants endorsed that they "got drunk" during the study period. Daily mean and variability of global PA and NA were compared between days with self-reported alcohol intoxication and days without self-reported alcohol intoxication. Trajectories of affect were modeled prior to and following episodes of self-reported alcohol intoxication. There were no differences in the mean or variability of PA or NA on days characterized by self-reported alcohol intoxication compared to days with no self-reported alcohol intoxication ( p s>0.05). PA decreased significantly prior to self-reported alcohol intoxication and remained stable afterwards. There were no changes in global NA before or after self-reported alcohol intoxication, but an examination of the facets of NA showed that sadness increased following episodes of self-reported alcohol intoxication. These findings showed only partial support for a negative reinforcement model of alcohol use in women with BN. Highlights: We modeled affect around episodes of intoxication in women with bulimia nervosa. No differences in mean affect on days characterized by intoxication. No differences in variability of affect on days characterized by intoxication. Positive affect decreased prior to episodes of intoxication. Sadness increased following episodes of intoxication.